2007
DOI: 10.1016/j.mce.2007.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Non-classical actions of the mineralocorticoid receptor: Misuse of EGF receptors?

Abstract: The mineralocorticoid receptor (MR) plays a key role in cardiovascular and renal injury. The underlying mechanisms seem to involve the epidermal growth factor receptor (EGFR) for the development of fibrosis and vascular dysfunction. Both enhanced EGFR transactivation by activated MR as well as upregulation of EGFR expression by aldosterone-bound MR have been described. While the former seems to be mediated by the tyrosine kinase cSrc, reporter gene assays and chromatin immunoprecipitation data indicate that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
30
0
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 58 publications
0
30
0
1
Order By: Relevance
“…On the basis of the observation that many genes regulated by MAPK are also controlled by NF-B, some studies have demonstrated that activation of p38 kinase and ERK pathways enhance the transactivation potential of p65/RelA. 29 Aldosterone activates MAPK through various mechanisms, including MR-dependent transactivation of the EGF receptor, 5 or redox-sensitive pathways. 6 Nevertheless, we found that several hours of aldosterone treatment did not alter the phosphorylation levels of ERK1/2 and decreased phosphorylation of p38 kinase, suggesting that the activity of these MAPK is unaltered or decreased, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of the observation that many genes regulated by MAPK are also controlled by NF-B, some studies have demonstrated that activation of p38 kinase and ERK pathways enhance the transactivation potential of p65/RelA. 29 Aldosterone activates MAPK through various mechanisms, including MR-dependent transactivation of the EGF receptor, 5 or redox-sensitive pathways. 6 Nevertheless, we found that several hours of aldosterone treatment did not alter the phosphorylation levels of ERK1/2 and decreased phosphorylation of p38 kinase, suggesting that the activity of these MAPK is unaltered or decreased, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Activation of the EGF receptor and mitogen-activated protein kinases (MAPK), induction of oxidative stress, and MR-dependent transcription of proinflammatory genes are some of the mechanisms proposed to account for the injurious effects induced by aldosterone. [5][6][7][8] As outlined by recent reports, mineralocorticoid also mediates inflammation and fibrosis through NF-B activation in liver, heart, and glomerular mesangial cells 9 -13 via a pathway involving the aldosterone early-induced gene, serum and glucocorticoid-induced kinase 1 (SGK1). 11,12 NF-B is a transcription factor composed of dimers of Rel family proteins (p65/RelA, p50/p105, p52/p100, RelB, and c-Rel).…”
mentioning
confidence: 99%
“…11 In cultured cells, downstream EGFR signaling cascades are induced by aldo or prevented by MR blockade on aldo stimulation. 12 Increases in EGFR expression and/or activation have been demonstrated after aldo stimulation, ex vivo after the incubation of rat aorta and renal, endothelial, and vascular smooth muscle cultured cells with aldo and in vivo in the aorta of adrenalectomized rats treated with aldo. [13][14][15][16] However, the consequences of EFGR activation to the vascular effects of aldo have not yet been demonstrated in vivo.…”
mentioning
confidence: 99%
“…One confounder may be that many studies, particularly those examining the coronary vasculature, use a longer period of mineralocorticoid/salt treatment, that is, 8 weeks. 6,7 Although these results may be interpreted as evidence that the in vitro studies 10 have not recapitulated the in vivo situation, there are the usual caveats. In any germline knockout mouse, the possibility that there is redundancy and/or compensatory mechanisms (which may be recruited during development) must be considered.…”
mentioning
confidence: 93%
“…This response appears to involve MR, but not in a classic genomic pathway; the activation involves the cytosolic tyrosine kinase cSrc, which is known to activate EGFR. 10 Activation of the EGFR and its downstream effectors, such as extracellular signal-regulated kinase, is proliferative, and, indeed, the effects of angiotensin on extracellular signalregulated kinase activity also involve the EGFR. GriolCharhbili et al 9 seek to directly address the role of the EGFR in mediating mineralocorticoid/salt-induced vascular damage in vivo.…”
mentioning
confidence: 99%